Distinct β-glucan molecules modulates differently the circulating cortisol levels and innate immune responses in matrinxã (Brycon amazonicus) - Franco Montoya, Luz Natalia [UNESP]; Favero, Gisele Cristina [UNESP]; Zanuzzo, Fabio Sabbadin [UNESP]; Urbinati, Elisabeth Criscuolo [UNESP] (Elsevier, 2018)
This study investigated the effects of two β-glucan molecules with different purities and isolated by different biotechnological processes on the immune response of matrinxã (Brycon amazonicus) prior and after challenge with Aeromonas hydrophila. In this sense, we evaluated serum cortisol and plasma glucose levels, the number of leukocytes (lymphocytes, neutrophils and monocytes), as well as the respiratory activity of leukocytes prior to, 6 and 24 h post infection (hpi). During 15 days, fish were fed with diets containing 0.1% of two β-glucans (β-G 1 and β-G 2, with 71 and 62% of purity, respectively) and then submitted to challenge. Results were compared with a positive control group fed with a β-glucan-free diet. A negative control group, also fed with β-glucan-free diet but inoculated with PBS, was established to evaluate the effect of handling during injection. Our results showed that different β-glucans affected differently the biological responses of matrinxã. The βG 2 modulated the cortisol profile prior to and after the acute infection with A. hydrophila, and increased the mobilization and activity of leukocytes. The infection promoted lymphopenia at 6 hpi and both β-glucans increased the circulating lymphocyte population 24 hpi. Moreover, the β-G 2 prevented the infection-induced neutrophilia at 6 and 24 hpi. Finally, the β-G 2 caused a marked increase in the circulating monocytes prior to infection, and a reduction at 6 hpi that was reversed at 24 hpi. In summary, our study demonstrates that β-G 2 was more efficient on the induction of the cell-mediate immunity in matrinxã.
Keywords: Cell-mediated immunity; Early defense; Immunostimulation; White blood cells